If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) + 6 = 2x + -5 Reorder the terms: 4(-3 + x) + 6 = 2x + -5 (-3 * 4 + x * 4) + 6 = 2x + -5 (-12 + 4x) + 6 = 2x + -5 Reorder the terms: -12 + 6 + 4x = 2x + -5 Combine like terms: -12 + 6 = -6 -6 + 4x = 2x + -5 Reorder the terms: -6 + 4x = -5 + 2x Solving -6 + 4x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + 4x + -2x = -5 + 2x + -2x Combine like terms: 4x + -2x = 2x -6 + 2x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + 2x = -5 + 0 -6 + 2x = -5 Add '6' to each side of the equation. -6 + 6 + 2x = -5 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = -5 + 6 2x = -5 + 6 Combine like terms: -5 + 6 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5
| 3/5v=30 | | 4=k/5 | | xcubed-2x=21 | | 3a+9b=9 | | 76.8=.32x | | 4a+6b=56 | | 9-6x=4x-3 | | F(x)=8000+(0.05)x | | 2=k/3 | | 9x+4=ew | | 6s+f=12 | | 2u+v=2 | | 2n/3-6/11=48/33 | | 2=9k | | (5x-10)(4x+12)= | | y^2-6y+x+5=0 | | x^3-3x^2-9x+7=0 | | -5x+26=-9 | | 13X/6=9 | | x+2-6=6x | | 7x-6-(8-2)= | | And+6a= | | 11+7=6x+7 | | 17-(6X-7)=6X | | 3(2a+2)-4(3a-5)= | | 7x-9-9x=6x+12 | | -5A+10=5 | | -2A+1=4 | | 3a+1=2x+4 | | 4=2x-10 | | y=(x-3)(x-3)+(x-9)(x-9) | | 3/4x=7/1 |